Pemanfaatan Podcast Mini Sebagai Media Untuk Meningkatkan Keterampilan Menyimak Bahasa Indonesia Di Kelas VI Sd Negeri 1 Sudimoro Tulung Klaten - Trimurtini .; Basuki .; Nanik Herawati; Hersulastuti . (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
Language plays a crucial role as the primary means of communication in human life. One of the language skills that students must master is listening, as this skill is fundamental to understanding spoken information. However, based on observations in sixth-grade students at SD Negeri 1 Sudimoro, students' listening skills are still relatively low. This is indicated by the low average class score, which has not yet reached the Minimum Completion Criteria (KKM), and the limited use of conventional learning media. Therefore, innovative, engaging learning media that aligns with technological developments are needed, one of which is the use of mini podcasts. This study aims to determine the effect of using mini podcasts on the Indonesian language listening skills of sixth-grade students at SD Negeri 1 Sudimoro in the 2025/2026 academic year. This study used a quantitative approach with an experimental research type, namely a pre-experimental design in the form of a One-Group Pretest–Posttest Design. The study subjects were 24 students. Data collection used a test method, while data analysis was conducted using descriptive and inferential statistics using the t-test. The results of the study showed an increase in students' listening skills, which was marked by an increase in the average score from 66.25 in the pretest to 83.13 in the posttest. The t-test results showed a calculated t value of 7.07 which was greater than the t table of 2.06 at a significance level of 0.05, so it can be concluded that the use of mini podcast media had a significant effect on improving the Indonesian listening skills of sixth-grade students of SD Negeri 1 Sudimoro.